Prevalence of Isolated Atrial Amyloidosis in Young Patients Affected by Congestive Heart Failure - Lia Millucci; Lorenzo Ghezzi; Giulia Bernardini; Daniela Braconi; Piero Tanganelli; Annalisa Santucci (The Scientific World Journal)
Atrial natriuretic peptide (ANP), whose amyloid is responsible of isolated atrial amyloidosis (IAA), is known to play an important role in the pathophysiology of congestive heart failure (CHF). We provide here the microscopic examination of atrial biopsies from 36 young (mean 40 years) CHF patients distinguished in idiopathic dilated cardiomyopathy (DC) affected and hypertrophic Cardiomyopathy (HC) affected, endorsing the presumptive association of early CHF with IAA. We utilized a multiple method, using Congo red (CR) staining, CR fluorescence (CRF), and immunohistochemistry to assess the presence of IAA in CHF. Immunostaining showed a moderate deposition of IAA in the atrium surrounding working myocardium with small intracellular deposits. Our findings suggest a monitoring of young CHF cases for the development of IAA. Our study also demonstrated how the concurrent use of immunohistochemistry, CR, and CRF may greatly enhance the detection of low-grade amyloid deposits.